Pembingkaian Pesan Dan Persepsi Risiko Psikologis Pada Isu Konsumen Hijau - Euis Soliha; H. Sophiyanto Wuryan (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2013)
The purpose of this research is to analyze the effect of the message framing on the perceived psychological risk on green environmental issues. Consumers nowadays have become more critical about issues on green consumer due to the increasing levels of consumers’ knowledge. Government and marketers also should perform active movement to increase consumers’ awareness of their environment. Those include giving a message to the consumers. When marketers deliver the message, they need to concern about message framing. Message framing is likely to influence the consumer's perception. Research design used in this study is design experiments. In this case the message was manipulated by message framing: positive and negative. The hypothesis of this study, H1: There are differences in perceived psychological risk perception on advertising by using positive and negative message framing, H2: There are differences in perceived psychological risk of consumers on advertising by using positive and negative framing that is reinforced with consumer knowledge. The analysis results of hypothesis 1 showed that there are significant differences in perceived psychological risk on advertising by using positive and negative message framing. Consumers feel that perceived psychological risk is lower in the ad with a positive message framing. Therefore, on advertising products related to green consumer issues, using positive message framing will be more effective. The analysis result of hypothesis 2 showed that there are no significant difference in perceived psychological risk on advertising by using positive and negative message framing that is reinforced by consumer knowledge. Consumer knowledge did not moderate the effect of message framing on perceived psychological risk.